FAKTOR YANG MEMPENGARUHI PERUBAHAN LABA PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Hutomo, Satrio (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to test some factors simultaneously and partially to the factors which have the influence to the profit changes at manufacturing companies in which these factors come from independent variables which consist of current ratio, quick ratio, total asset turn over, debt to total asset ratio and return on equity variables. The result of simultaneous test shows that independent variables simultaneously have an influence to the dependent variable which is profit change is 20.2% and result of partial test shows that independent variables have no significant influence to the dependent variable which is profit change, which is indicated by signification level which is obtained from independent variables which are current ratio is 0.206, quick ratio is 0.838, total asset turnover is 0.776, debt to total asset ratio is 0.674 and return of equity is 0.823 which is bigger than Î± = 5% (0.05). The result shows that these factors have insignificant influence to the profit change. Keywords: Financial ratio influence to the profit change